Association of tumor‐infiltrating lymphocytes before and after neoadjuvant chemotherapy with pathological complete response and prognosis in patients with breast cancer. (25th September 2021) - Hong, Jin; Rui, Weiwei; Fei, Xiaochun; Chen, Xiaosong; Shen, Kunwei
Abstract: Purpose: To evaluate the predictive and prognostic value of tumor‐infiltrating lymphocytes (TILs) before and after neoadjuvant chemotherapy (NAC) in patients with breast cancer. Patients and methods: Consecutive breast cancer patients treated with NAC between August 2008 and November 2019 were retrospectively analyzed. TIL levels were evaluated of invasive tumor samples, and high expression was defined as TILs >10%. Total pathological complete response (pCR) was defined as no invasive tumor in the breast or lymph nodes. Univariate and multivariate analyses were used to assess factors associated with pCR rate, disease‐free survival (DFS), and overall survival. Results: A total of 461 patients were included. The mean pre‐NAC TIL level was higher among patients with pCR than among patients without pCR (24.28% ± 2.34% vs. 11.34% ± 0.60%, respectively, p < 0.0001). The multivariate analysis demonstrated that a high pre‐NAC TIL level was an independent risk factor for a higher pCR (odds ratio = 3.92, 95% CI = 2.23–6.90, p < 0.001). Patients with high pre‐NAC TIL levels had a better 5‐year DFS than those with low pre‐NAC TIL levels (84.5% vs. 68.9%, HR = 0.50, 95% CI = 0.31–0.81, p = 0.005). The multivariate analysis showed that pre‐NAC TIL (HR = 0.48; 95% CI = 0.29–0.81, p = 0.006) but not post‐NAC TIL (HR = 0.89, 95% CI = 0.50–1.59, p = 0.699) was significantly associated with DFS among patients without pCR. Furthermore, patients with low pre‐ and post‐NAC TIL levels had a worse 5‐year DFS than those with high pre‐NAC TIL levels (HR = 2.09, 95% CI = 1.23–3.56, p = 0.007). Conclusions: Pre‐NAC TIL level can predict pCR and DFS in patients with breast cancer receiving NAC. For patients without pCR, pre‐NAC TIL, and TIL category change, but not post‐NAC TIL, were significantly associated with DFS.